2008
DOI: 10.1200/jco.2007.15.1613
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cells in Head and Neck Squamous Cell Cancer

Abstract: Appropriate treatment of head and neck squamous cell cancer (HNSCC) remains one of the most difficult challenges in head and neck oncology. Overall survival of patients with HNSCC remains at approximately 50% at 5 years. Surgical therapy can be mutilating and often has significant effects on swallowing, speech, and physical appearance. The addition of chemotherapy to radiation treatment has shown efficacy in organ preservation in some sites in the head and neck, but has resulted in limited improvement in survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
135
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(146 citation statements)
references
References 36 publications
6
135
0
5
Order By: Relevance
“…The following are key features of cancer stem cell hypothesis (Prince et al, 2008): i) Only a small fraction of the cancer cells within a tumor have tumorigenic potential when transplanted into immunodeficient mice;…”
Section: The Cancer Stem Cell Hypothesismentioning
confidence: 99%
“…The following are key features of cancer stem cell hypothesis (Prince et al, 2008): i) Only a small fraction of the cancer cells within a tumor have tumorigenic potential when transplanted into immunodeficient mice;…”
Section: The Cancer Stem Cell Hypothesismentioning
confidence: 99%
“…The cancer stem cell hypothesis states that a subpopulation of cells in cancerous tissues with tumor inducing capacity as well as stem cell-like characteristics is responsible for carcinogenesis. These cells are termed as cancer stem cells [2]. However, studies on the molecular mechanisms related to cancer stem cells remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that CSCs exist in various tumor types and the signaling pathways involved in CSC self-renewal and differentiation seems to be common in different tumor types (Boman and Huang, 2008;Dirks, 2008;Huff and Matsui, 2008;Kakarala and Wicha, 2008;Prince and Ailles, 2008;Sell and Leffert, 2008;Takaishi et al, 2008). Therefore, there is the possibility that therapies targeting these common pathways be effective against a wide spectrum of tumor types.…”
Section: Resultsmentioning
confidence: 99%